Application of The Simplex Method in Crop Planning. - Masereka, Joel (Kabale University, 2024)
In this study, the researcher intended to propose and investigate a model that describes how a farmer can allocate his land to three crops namely; maize, groundnuts, and beans, to maximize yields and consequently maximize profits, given that he has 20 acres of land and other resources amounting to 5,800,000 shillings to be spent on inputs, and 7,500,000 to be spent on labor. 'it further shows that, after applying the simplex method to the model, beans are more profitable compared to groundnuts and maize. Furthermore, we show that the farmer can make a maximum profit of 14,058,765 shillings if he plants 14.94 acres of land. This indicates that farming beans pay much better than farming groundnuts and maize.